Photoluminescence recovery by in-situ exposure of plasma-damaged n-GaN to atomic hydrogen at room temperature - Shang Chen; Yi Lu; Ryosuke Kometani; Kenji Ishikawa; Hiroki Kondo; Yutaka Tokuda; Makoto Sekine; Masaru Hori (AIP Advances, 2012)
The effect of in-situ exposure of n-GaN damaged by Cl2 plasma to atomic hydrogen (H radicals) at room temperature was investigated. We found that the PL intensities of the band-edge emission, which had been drastically reduced by plasma-beam irradiation at a Cl ion dose of 5 × 1016 cm−2, recovered to values close to those of as-grown samples after H radical exposure at a dose of 3.8 × 1017 cm−2. XPS revealed the appearance of a peak at a binding energy of 18.3 eV, which is tentatively assigned to Ga-H, and confirmed the removal of Cl after H radical exposure.